A Systematic Review and Meta-analysis of the Therapeutic Effect of Acupuncture on Migraine - Ou, Ming-Qian; Fan, Wei-Hao; Sun, Fu-Rong; Jie, Wan-Xin; Lin, Mei-Jun; Cai, Yu-Jie; Liang, Shi-Yun; Yu, Yang-Sheng; Li, Min-Hua; Cui, Li-Li; Zhou, Hai-Hong (Frontiers in Neurology, 2020)
Background Migraine is an intractable headache disorder, manifesting as periodic attacks. It is highly burdensome for patients and society. Acupuncture treatment can be beneficial as a supplementary and preventive therapy for migraine. Objectives This systematic review and meta-analysis aimed to investigate the efficacy and safety of acupuncture for migraine, and to examine transcranial doppler changes after acupuncture. Methods Reports, conference and academic papers published before March 15, 2019 in databases including PubMed, Cochrane library, Embase, China National Knowledge Infrastructure, WANFANG Database, Chinese journal of Science and Technology, and China Biomedical were searched. Randomized controlled trials (RCTs) involving acupuncture, sham acupuncture, and medication in migraine were included. The Cochrane Collaboration software, RevMan 5.3, was used for data processing and migration risk analysis. Results Twenty-eight RCTs were included. 15 RCTs included medication only, 10 RCTs included sham acupuncture only, and 3 RCTs included both. The study included 2874 patients, split into 3 groups: acupuncture treatment group (n = 1396), medication control group (n = 865), and sham acupuncture control group (n = 613). The results showed that treatment was more effective in the acupuncture group than in the sham acupuncture group (MD = 1.88, 95% CI [1.61, 2.20], P < 0.00001) and medication group (MD = 1.16, 95% CI [1.12, 1.21], P < 0.00001). Improvement in visual analogue scale (VAS) score was greater in the acupuncture group than in the sham acupuncture group (MD = -1.00, 95% CI [-1.27, -0.46], P < 0.00001; MD = -0.59, 95% CI [-0.81, -0.38], P < 0.00001), and their adverse reaction rate was lower than that of the medication group (RR = 0.16, 95% CI [0.05, 0.52], P = 0.002). The improvement of intracranial blood flow velocity by acupuncture is better than that by medication, but the heterogeneity makes the result unreliable. Conclusions Acupuncture reduced the frequency of migraine attacks, lowered VAS scores, and increased therapeutic efficiency compared with sham acupuncture. Compared with medication, acupuncture showed higher effectiveness with less adverse reactions and improved intracranial blood circulation. However, owing to inter-study heterogeneity, a prospective, multicenter RCT with a large sample is required to verify these results.